CCAAT/Enhancer-Binding Protein β Mediates Oxygen-Induced Retinal Neovascularization via Retinal Vascular Damage and Vascular Endothelial Growth Factor - Tingting Li; Xuan Cai; Xiangning Wang; Xueyan Zhang; Hui Zhang; Biwei Xu; Shiwei Li; Jianyan Hu; Qiang Wu (Journal of Diabetes Research)
Objective. To evaluate the role of CCAAT/enhancer-binding protein β (C/EBP β) in retinal neovascularization (RNV) in an oxygen-induced retinopathy (OIR) model. Methods. Rats with OIR were exposed to alternating hypoxic and hyperopic conditions for 14 days. Then, the rats with OIR were assigned randomly to groups that received intravitreal injections of either shRNA lentiviral particles targeting C/EBP β (LV.shC/EBP β) or control particles (LV.shScrambled). The effectiveness of transduction using intravitreal injection of C/EBP β shRNA was examined in rats with OIR. The retinal vascular damage and accumulation of RNV were determined by retinal fluorescein-dextran perfusion, retinal ADPase staining, and periodic acid-Schiff (PAS) staining. Retinal function was recorded by electroretinogram responses to full-field light flashes. Reverse transcriptase-polymerase chain reaction (RT-PCR) and western blot analyses were used to measure mRNA and protein levels of C/EBP β and vascular endothelial growth factor (VEGF). The expression of p-C/EBP β was also examined by western blot analyses. The location of C/EBP β expression in the retina was determined by immunohistochemistry. Results. In OIR rats, the expression levels of C/EBP β and VEGF were significantly increased at both the mRNA and protein levels (P<0.01). The p-C/EBP β expression was consistent with the level of C/EBP β. C/EBP β was predominantly localized to the ganglion cell layer (GCL) and the inner nuclear layer (INL). The retinal C/EBP β level was significantly reduced in tissues from rats with OIR transduced with LV.shC/EBP β compared with tissues from those transduced with LV.shScrambled (P<0.01). Compared with those of the rats with OIR in the LV.shScrambled group, nonperfused retinal areas, neovascular tufts, pericyte death, and the ratio of endothelial cells to pericytes in the LV.shC/EBP β group were significantly reduced. In OIR rats, retinal function was impaired. There was no significant change in retinal dysfunction between the LV.shC/EBP β group and the LV.shScrambled group. The levels of VEGF mRNA and protein in the LV.shC/EBP β group were also decreased significantly compared with those of the rats with OIR in the LV.shScrambled group (P<0.01). Conclusions. C/EBP β shRNA inhibits RNV in OIR. A potential mechanism may be that the activity of C/EBP β increases with its overexpression, which in turn aggravates the amount of the retinal vascular damage and promotes transcription of VEGF. C/EBP β might be a new therapeutic target for preventing RNV.